FT-IR and FT-Raman spectroscopic studies of adsorption of isoniazid by montmorillonite and saponite - AKYÜZ, ZEKİ TANIL; AKYÜZ, SEVİM (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2008)
The adsorption of isoniazid on natural montmorillonite and saponite from Anatolia was investigated by FT-IR and FT-Raman spectroscopy. The intercalation of isoniazid within these clays has been shown by Xray diffraction to increase the interlayer spacing. Vibrational spectroscopy indicates that isoniazid molecules, intercalated into the layers of montmorillonite or saponite, are coordinated to exchangeable cations directly or indirectly through water bridges. It is concluded that the endocyclic nitrogen is mainly involved in the coordination. The carbonyl group oxygen, however, may be involved in a weak H-bonding interaction with water molecules. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: adsorption; clay minerals; 1R and Raman spectroscopy; Isoniazid; montmorillonite; saponite; emme; kil mineralleri; 1R ve Raman spektroskopisi